Ototoxicity in locally advanced head and neck cancer patients treated with induction chemotherapy followed by intermediate or high‐dose cisplatin‐based chemoradiotherapy. Issue 2 (7th December 2018) - Driessen, Chantal M. L.; Leijendeckers, Joop; Snik, Ad; van der Graaf, Winette T. A.; de Boer, Jan Paiul; Gelderblom, Hans; Kaanders, Johannes H. A. M.; Takes, Robert; van Herpen, Carla M. L.
Abstract: Background: This study evaluated ototoxicity in locally advanced head and neck cancer patients treated in the CONDOR study with docetaxel/cisplatin/5‐fluorouracil (TPF) followed by conventional radiotherapy with concomitant cisplatin 100 mg/m 2 on days 1, 22, and 43 (cis100+RT) versus accelerated radiotherapy with concomitant cisplatin weekly 40 mg/m 2 (cis40+ART). Methods: Sixty‐two patients were treated in this study. Audiometry was performed at baseline, during TPF, before start of chemoradiotherapy, and 1, 4, 8, and 12 months after treatment. Results: A complete dataset of audiometric data was available of 12 patients treated with high‐dose cisplatin and of 11 patients treated with intermediate‐dose cisplatin. Patients in the high‐dose group showed significant more hearing loss than in the intermediate group at 4 kHz ([ z = 1.98; P = .04] and 8 kHz [ z = 2.07; P < .03]). Interindividual variation was high in both groups. Conclusion: After induction TPF, more ototoxicity was observed in chemoradiotherapy with cis100+RT than after chemoradiotherapy with cis40+ART.